2011
DOI: 10.1001/archneurol.2011.150
|View full text |Cite
|
Sign up to set email alerts
|

Using Positron Emission Tomography and Florbetapir F 18 to Image Cortical Amyloid in Patients With Mild Cognitive Impairment or Dementia Due to Alzheimer Disease

Abstract: To characterize quantitative florbetapir F 18 (hereafter referred to as simply florbetapir) positron emission tomographic (PET) measurements of fibrillar ␤-amyloid (A␤) burden in a large clinical cohort of participants with probable Alzheimer disease (AD) or mild cognitive impairment (MCI) and older healthy controls (OHCs). Design: Cerebral-to-whole-cerebellar florbetapir standard uptake value ratios (SUVRs) were computed. Mean cortical SUVRs were compared. A threshold of SUVRs greater than or equal to 1.17 wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

22
287
4
3

Year Published

2011
2011
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 315 publications
(316 citation statements)
references
References 38 publications
(21 reference statements)
22
287
4
3
Order By: Relevance
“…5,11 These findings motivated quantitative analysis of [ 18 F] florbetapir PET brain images, comparing differential binding between these cortical regions to the whole cerebellum, a site not prone to amyloid deposition, expressed as cerebral-to-whole-cerebellar standardized uptake value ratios (SUVr). 5,12 Subsequent pathologic analysis demonstrated high sensitivity (97%), specificity (100%), and accuracy (98%) between [ 18 F] florbetapir PET SUVr and postmortem immunohistochemical measurements of ␤-amyloid. 5,7,12 These studies showed that a mean [ 18 F] florbetapir SUVr value of Ͼ1.17 was strongly associated with an intermediate-to-high likelihood of a neuropathologic diagnosis of AD.…”
mentioning
confidence: 99%
“…5,11 These findings motivated quantitative analysis of [ 18 F] florbetapir PET brain images, comparing differential binding between these cortical regions to the whole cerebellum, a site not prone to amyloid deposition, expressed as cerebral-to-whole-cerebellar standardized uptake value ratios (SUVr). 5,12 Subsequent pathologic analysis demonstrated high sensitivity (97%), specificity (100%), and accuracy (98%) between [ 18 F] florbetapir PET SUVr and postmortem immunohistochemical measurements of ␤-amyloid. 5,7,12 These studies showed that a mean [ 18 F] florbetapir SUVr value of Ͼ1.17 was strongly associated with an intermediate-to-high likelihood of a neuropathologic diagnosis of AD.…”
mentioning
confidence: 99%
“…This was reflected in a recent study using florbetapir, which showed significant overlap between scans of patients with probable AD, patients with MCI, and older healthy controls (Fig. 4) [8]. These observations severely limit the utility of this PET imaging approach for accurately diagnosing the presence or absence of MCI, let alone early AD.…”
Section: Theoretical Basis Of Amyloid Imagingmentioning
confidence: 93%
“…Patients with MCI, early AD, and late AD are assumed to have roughly 0.1%, 1%, and 6% of total cortical area (i.e., area fractions f a ) occupied by β-amyloid, respectively, and corresponding volume fractions (f v ) of roughly 0.03%, 0.33%, and 2.0%, respectively Fig. 4 A scatterplot of mean cortical SUV ratios in individuals with probable AD (PAD) and mild cognitive impairment (MCI), as well as older healthy controls (OHC) [8]. Noteworthy false-negative and false-positive rates can be seen in AD patients and controls, respectively (reproduced with permission from Archives of Neurology, [8]) established, the claim of causation is still a matter of debate and has recently been challenged by developments in the clinical trials of antiamyloid pharmaceuticals.…”
Section: Theoretical Basis Of Amyloid Imagingmentioning
confidence: 99%
See 2 more Smart Citations